ELECTORAL SYSTEM IN THE STATE’S POLITICAL FIELD - Шмат, А.С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article deals with the concept of the electoral system and approaches to its interpretation. The specific place of the electoral model in the electoral law is defined. Areas of the electoral model influence on the country's political field are defined. The role of electoral rules in the functioning of the state is analyzed. The meaningful characteristics of electoral systems and features of their impact on the political process are described.